2014
DOI: 10.3727/096368912x662408
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Mechanisms by which Neural Precursors Augment Recovery following Spinal Cord Injury: A Key Role for Remyelination

Abstract: The mechanisms by which neural precursor cells (NPCs) enhance functional recovery from spinal cord injury (SCI) remain unclear. Spinal cord injured rats were transplanted with wild-type mouse NPCs, shiverer NPCs unable to produce myelin, dead NPCs, or media. Most animals also received minocycline, cyclosporine, and perilesional infusion of trophins. Motor function was graded according to the BBB scale. H&E/LFB staining was used to assess gray and white matter, cyst, and lesional tissue. Mature oligodendrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 73 publications
3
41
0
Order By: Relevance
“…These data are supported by work done by our laboratory and others that has examined aNPCs isolated from wt-and shi-mice [34,42]. Yasuda et al [34] observed locomotor recovery following SCI with wt-aNPC transplantation but not shi-aNPC.…”
Section: Discussionsupporting
confidence: 74%
“…These data are supported by work done by our laboratory and others that has examined aNPCs isolated from wt-and shi-mice [34,42]. Yasuda et al [34] observed locomotor recovery following SCI with wt-aNPC transplantation but not shi-aNPC.…”
Section: Discussionsupporting
confidence: 74%
“…The transplanted cells also expressed markers of NPCs, neurons, and astrocytes, suggesting sustained multi-potency, and differentiated into neural cells in the injured environment, in accordance with other stem cells [1,2,4]. All of this directly supports Previous studies have demonstrated that remyelination after transplantation of NPCs contributes to functional recovery [6,15], as NPCs isolated from Shiverer mice -MBP null mice that do not form compact myelin -do not show the remyelination effect as NPCs from wild-type mice. In this study, promotion of remyelination contributed predominantly to functional recovery, more than glial scar reduction (Figs.…”
Section: Discussionsupporting
confidence: 75%
“…Of particular interest are neural precursor cells (NPCs) which can differentiate into both neurons and glia [13]. NPCs have been shown to promote remyelination [14,15] and support functional recovery [16], making them very promising for the treatment of spinal cord injuries. Unfortunately, transplanted cells have poor survival rates.…”
Section: Introductionmentioning
confidence: 99%